2008
DOI: 10.1097/ccm.0b013e31817d7912
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin during porcine aortic balloon occlusion-induced ischemia/reperfusion injury

Abstract: During porcine aortic occlusion-induced ischemia/reperfusion erythropoietin improved kidney function and spinal cord integrity. The lacking effect on spinal cord function was most likely the result of the pronounced neuronal damage associated with the longlasting ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 51 publications
4
40
4
1
Order By: Relevance
“…Anesthesia and surgical instrumentation were performed as in previous experiments [4,15]. After induction of anesthesia with iv propofol and ketamine and subsequent endotracheal intubation, anesthesia was maintained with continuous iv propofol (6-8 mg kg -1 h -1 ) and remifentanil (15-20 lg kg -1 h -1 ).…”
Section: Surgical Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthesia and surgical instrumentation were performed as in previous experiments [4,15]. After induction of anesthesia with iv propofol and ketamine and subsequent endotracheal intubation, anesthesia was maintained with continuous iv propofol (6-8 mg kg -1 h -1 ) and remifentanil (15-20 lg kg -1 h -1 ).…”
Section: Surgical Preparationmentioning
confidence: 99%
“…Recombinant human erythropoietin (rhEPO) protected against spinal cord I/R injury [2,3], and, in fact, we previously showed in swine that 300 IU kg -1 rhEPO prior to aortic balloon occlusion and during early reperfusion reduced both thoracic spinal cord neuronal damage and glial apoptosis. Motor neuron function, however, did not recover, most likely due to the low dose of rhEPO administered and/or as a result of the marked tissue damage [4]. Moreover, Ehrenreich et al [5] recently reported a significantly higher overall death rate in rhEPO-treated patients with stroke, possibly as a result of the high number of patients undergoing systemic thrombolysis with recombinant tissue plasminogen activator: in vitro, a single rhEPO exposure enhances production of plasminogen activator inhibitor-1 [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simon et al 13 reported that EPO, administered immediately before ischemia and additionally after reperfusion, did not improve neurological recovery following spinal cord ischemia. Forty-five minutes of aortic occlusion was applied to the swine for this study, and both EPO-treated and saline-treated animals presented totally paralyzed lower extremities with marked histological injury.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Briefly, mice were anesthetized using tribromoethanol, and rectal temperature was maintained at 37°C. For this purpose, three gold electrodes were inserted into the scalp and one into the soft palate to apply electric impulses (MultiPulse Stimulator D185-Mark, Digitimer LTD) to the motor cortex to quantify MEPs.…”
Section: Electrophysiologymentioning
confidence: 99%